Ennui in Long-Term Cancer: Existential Consequences Experienced by an Academic - Annette M Lane RN, PhD (Journal of Patient Experience)
Individuals with long-term, incurable cancer may experience ennui. Ennui, a state of boredom, dissatisfaction and weariness may arise from not being able to engage regularly in meaningful activities. Not being able to take part in purposeful work or activities may result in existential issues that individuals with incurable cancer struggle to address. Within this article, the experiences of an academic experiencing ennui because of incurable cancer will be presented.